Condensation heat transfer on single horizontal smooth and finned tubes and tube bundles for R134a and propane - Gebauer, Thomas; Al-Badri, Alaa; Gotterbarm, Achim; El Hajal, Jean; Leipertz, Alfred; Fröba, Andreas Paul (International Journal of Heat and Mass Transfer, 2013)
For the refrigerants 1,1,1,2-tetrafluoroethane (R134a) and propane (R290), the condensation heat transfer was investigated on coated and uncoated horizontal smooth, standard finned and high performance tubes by experiments and computational fluid dynamics (CFD)-simulations. Measurements were carried out at a saturation temperature of 37 degrees C varying the heat flux between 4 kW m(-2) and 102 kW m(-2). In comparison to the Nusselt theory, enhancement factors of 12.8 to 30.2 were experimentally found for single standard finned and single high performance tubes. For both refrigerants, the high performance tubes showed a larger bundle effect than the standard finned tubes, although the latter show a lower heat transfer performance. In general, experimental results for coated tubes show a slightly lower heat transfer performance and no improvements of the condensate drainage could be observed for the modification. CFD-simulations were used to predict the condensation heat transfer on single tubes for the first time. Our experimental data and CFD-simulations were compared with analytical models available in the literature. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Bundle effect; CFD; Coating; Condensation heat transfer; Horizontal tubes; R134a; R290

Element by element prediction model of condensation heat transfer on a horizontal integral finned tube - Al-Badri, Alaa; Gebauer, Thomas; Leipertz, Alfred; Fröba, Andreas Paul (International Journal of Heat and Mass Transfer, 2013)
The paper presents an analytical model to calculate the condensation heat transfer coefficient on an integral finned tube. The model depends on elemental calculations by dividing the tube wall into small annular elements. It takes into consideration the local temperature distribution on the outside surface of the finned tube, the local heat transfer rate and the height of condensate in the channel between fins. The model is able to predict the heat transfer for different fin profiles. Gravity force and surface tension forces are included in the model, where for the latter a linear pressure distribution over the fin is assumed. For the verification of the present model, experimental data for a copper standard finned tube with 1, 1, 1, 2-tetrafluoroethane (R134a) and propane (R290) from our experimental work were used. Within this work, experiments were performed for a steel standard finned tube with R290. For tubes having more than 40 fins per inch (FPI), it could be shown that the channel between fins can be approximated to be trapezoidal or rectangular. This approximation is also applicable for the condensation on tubes having 26 FPI or larger if the subcooling between the saturated vapour and the tube wall is larger than a certain value depending on the working fluid. In comparison to previous analytical models, the present model agrees well with the experimental data and predicts these data with a mean absolute percentage deviation of 4.7%. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Analytical model; Condensation; Finned tube; Heat transfer coefficient; Temperature distribution

The influence of fin structure and fin density on the condensation heat transfer of R134a on single finned tubes and in tube bundles - Al-Badri, Alaa; Bär, Andreas; Gotterbarm, Achim; Rausch, Michael Heinrich; Fröba, Andreas Paul (International Journal of Heat and Mass Transfer, 2016)
The influence of fin structure and density on the condensation heat transfer of refrigerant 1,1,1,2-tetrafluoroethane (R134a) is investigated on single finned tubes and in corresponding bundles. Experiments have been performed on standard and enhanced finned tubes with 39, 48, and 56 fins per inch (FPI) and different fin heights. The enhanced finned tubes are based on the standard ones, and are characterized by a non-uniform fin structure. The condensation heat transfer coefficient (HTC) is determined for single tubes as well as for each row of the tube bundles and compared with predictions from analytical models. In the single tube measurements, the enhanced finned tubes showed distinctly higher HTCs than the standard finned tubes. Different condensation flow modes have been observed during the tube bundle experiments where the additional structures on the fin flank of the enhanced finned tubes promote sheet mode condensation. It has been demonstrated that the standard finned tubes show a lower decrease in the condensation HTC with increasing tube row number in the bundle than the enhanced finned tubes. Among the standard finned tubes, the one with 48 FPI and larger fin height exhibits the highest HTCs for single tube and tube bundle experiments. The increase in the fin height seems to delay the formation of sheet mode condensation and thus to increase the condensation HTC. Among the enhanced finned tubes, the tube with 39 FPI yields the highest HTCs for both single tube and tube bundle measurements. Low fin density and large fin height obviously tend to keep the insulating effect of retained condensate in the fin channels low. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Bundle effect; Condensation; Fin height; Fin pitch; Fin structure; R134a